Pertumbuhan Penjualan, Ukuran Perusahaan, Return On Asset Dan Struktur Modal Terhadap Nilai Perusahaan Pada Perusahaan Yang Tercatat Pada Indeks LQ 45 - sandag, Norce Jelly (JURNAL RISET BISNIS DAN MANAJEMEN, 2015)
The purpose of establishing a corporation is to prosper the owner or the shareholders of the company. That purpose can be achieved by increasing the value of the company. Company value is very essential, since company with high value means the prosperity of the shareholders are also increased. The aim of this research is to examine the growth of Sales Growth, Company Size, ROA, and Capital Structure to the Company Value on companies listed in LQ 45 Index. The data period of this research is from 2009 to 2013. Sampling technique used was purposive sampling and 20 companies were used as the sample for this research. Data was analyzed using the multiple linear regression analysis. Based on the data analysis, it is found that Sales Growth has a positive insignificant effect on Company Value, Company Size affects negatively on Company Value, while ROA and Capital Structure have significant positive effects on Company Value. Keywords: Sales Growth, Company Size, Return on Asset, Capital Structure.